Quality assessment of short videos on health science popularization in China: scale development and validation - Xuan, Wenxia; Tian, Kun; Hao, Lijie (Frontiers in Public Health, 2025)
BackgroundShort videos that popularize health science have become essential for disseminating health information and enhancing public health literacy. However, previous research has primarily focused on health information content, with a significant gap in assessing the quality of health science popularization in short videos.MethodsThis study developed a quality assessment scale for the popularization of health science short videos based on multimodal theory, utilizing literature analysis and the creation of custom measurement items. Data were collected from scales completed by 796 residents through online surveys conducted on mobile devices. Both exploratory and confirmatory factor analyses were employed to evaluate the quality of mobile health science popularized short videos.ResultsThe results revealed that the quality scale for health science popularization in short videos could be divided into seven dimensions and 22 indicators, each a significant determinant of video quality.ConclusionThis research provides a more intuitive, reliable, and standardized tool for assessing the quality of health science popularization in short videos. Also, it offers essential guidance for the future design, development, and promotion of short health science popularization videos.